2015
DOI: 10.1210/jc.2015-2012
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Performance at Late Adolescence and the Risk for Impaired Fasting Glucose Among Young Adults

Abstract: Context:Although dysglycemia is a risk factor for cognitive decline, it is unknown whether cognitive performance among young and apparently healthy adults affect the risk for impaired fasting glucose (IFG).Objective: This study aimed to characterize the relationship between cognitive function and the risk for IFG among young adults. Design and Setting:This was a retrospective cohort study utilizing data collected at pre-military recruitment assessments with information collected at the screening center of Isra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…This is consistent with previous studies by the same research group, where cognitive function at age 11 has been shown to be associated with type 2 diabetes status and HbA 1c levels at the age of 70 [29,30]. In line with this, lower cognitive function at late adolescence (age 17 years) has been associated with elevated risk for impaired fasting glucose and future type 2 diabetes [31,32]. Furthermore, Altschul et al [7] showed that poorer cognitive function at the age of 70 is associated with increasing HbA 1c levels over the following decade.…”
Section: Lower Cognitive Dysfunction Precedes Type 2 Diabetessupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previous studies by the same research group, where cognitive function at age 11 has been shown to be associated with type 2 diabetes status and HbA 1c levels at the age of 70 [29,30]. In line with this, lower cognitive function at late adolescence (age 17 years) has been associated with elevated risk for impaired fasting glucose and future type 2 diabetes [31,32]. Furthermore, Altschul et al [7] showed that poorer cognitive function at the age of 70 is associated with increasing HbA 1c levels over the following decade.…”
Section: Lower Cognitive Dysfunction Precedes Type 2 Diabetessupporting
confidence: 91%
“…In addition, the findings by Altschul et al [7], along with others [29][30][31][32], support the concept that early-life cognitive function is associated with the risk for developing type 2 diabetes (or related characteristics, such as poor glycaemic control) in late life. This underlies the hypothesis that early adolescents with lower cognitive function may be at risk for developing type 2 diabetes later in life, and that there may be value in targeting preventive intervention strategies at this age group.…”
Section: Perspectivementioning
confidence: 67%
“…It has been reported that lower cognitive function during late adolescence is independently associated with an elevated risk for impaired fasting glucose and diabetes 26,27. We demonstrated in our previous report that patients with T2DM tended to have a preference for risk-seeking compared to those with T1DM.…”
Section: Discussionmentioning
confidence: 48%
“…[1315] Investigators from the Metabolic, Lifestyle and Nutrition Assessment in Young Adults (MELANY) study observed that, among young Israeli adults, those with the lowest level of cognitive function had two-fold increased risk for developing diabetes or impaired fasting glucose, compared to individuals with the highest level of cognitive function after adjustment for diabetes risk factors. [14, 15] Data from Elderly Nutrition and Health Survey in Taiwan (NAHSIT Elderly) showed older women with cognitive impairment had a significant 2.4-fold greater risk for developing diabetes compared to those without cognitive impairment, while in elderly men this association was more modest and not statistically significant. [13] Several factors may have contributed to our finding that cognitive function was not associated with incident diabetes in the same magnitude as previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…[1315] However, determination of baseline brain health in these studies is limited to cognitive assessment only. Wechsler noted that factors not indicative of cognitive function per se, such as experience and familiarity with testing and socioeconomic structures, may influence performance on cognitive assessments.…”
Section: Introductionmentioning
confidence: 99%